The Analysis of Differentiation of Driving Behavior towards Violations and Accidents based on Demographics Aspect at Lombok Island – West Nusa Tenggara - I Wayan Suteja; I A O Suwati Sideman; I Gde Putu Warka (Postgraduate, University of Mataram, 2023)
Based on the accident data’s, which recorded that 2016 until 2019, there were everage 225 traffic accidents involving students and college student riders. From these accident data’s, was found that the male rider dominated traffic accidents than female rider. This study aims to determine how a simple model can be done based on difference a demographic aspect such as differences of gender influences, differences of economic and social aspect on the driving behavior of student and college students on traffic accidents in Mataram City. The Structural Equation Modeling (SEM) method, with the help of the AMOS program was used in this study. The number of respondents in this study were 792 people, consisting of 391 students and 391 college students. The model in this study consisted of 3 variables, namely behavior, violations and accidents. Driving behavior has a significant effect on traffic violations with a probability value (P) = 0.000 (<0.001), and a testing value of C.R> 1.64. The size of the estimated value in the student group shows that the effect of behavior on violations in male student rider is 30.08% stronger than that of female rider. And the effect of behavior on violations among female students is 0.8% stronger than college students. Traffic violations have a significant effect on traffic accidents with a probability value of 0.000 (<0.01), and a test value of C.R> 1.96. Traffic violations on male students have an effect on accidents by 0.992, 50.1% stronger than female students. The effect of traffic violations on student rider on accidents is 2.44% stronger than female student rider. Gender differences have a significant effect on driving behavior based on the probability value (P) = 0.000 (<0.001). On the otherhand, the results of the analysis show that the driving behavior model of the community on the Mataram City based on the review of the economic and social aspects shows a model with a variety of patterns where the GRDP review follows the Polynomial model, based on the number of cityzen population, the tendency of the Exponential model and the review of the gender probability aspect follows the Logarithmic model pattern